Comparison of alcohol shock enrichment and selective enrichment for the isolation of Clostridium difficile - Riley, T.V.; Brazier, J.S.; Hassan, H.; Williams, K.; Phillips, K.D. (1987)
Two enrichment methods were compared for their ability to recover Clostridium difficile from stool samples. One method used selective enrichment in an antibiotic-containing broth followed by detection with a latex particle agglutination (LPA) reagent. The other used enrichment in a non-selective broth following treatment of the specimen with alcohol. With clinical specimens enrichment culture was significantly more successful at detecting C. difficile than direct plating. Alcohol shock enrichment was twice as effective as direct culture, while selective broth enrichment was three times more effective. The use of LPA for screening selective enrichment broths for C. difficile should prove a cost-effective measure as only positive broths (about 20) require subculture for confirmation.